AGRICULTURAL WASTES BASED FIBROUS POZZOLANIC CONCRETE AS A GREEN CONSTRUCTION MATERIAL - CHANDRAN, RATANASHANGKARI (IRC, 2017)
Concrete, made up of Portland cement, aggregates and water, is the most crucial construction material used for various infrastructures over the centuries. An integrated problem related to the concrete industry such as carbon emission and durability drawback, and underutilization of agricultural wastes in Malaysia has led to the development of pozzolans as cement replacement material and natural fibres as concrete reinforcement materials. This project formulates brick combinations of ‘Fibrous Pozzolanic Concrete’, incorporating both pozzolans and natural fibres made from agricultural waste materials that are underutilized in Malaysia, to further reduce carbon emission due to cement manufacturing, as well as to improve the performance and sustainability of concrete. From the performance evaluation and microstructural analysis, it has been found that Palm Oil Fuel Ash is an ideal cement replacement material as its designs of 15% cement replacement level (PO15 and PC15) yields comparable compressive strength (27.66 MPa and 24.40 MPa respectively) with Control (25.24 MPa). However, PO15 and PC15 is more prone to acid and alkali attack with mass loss of 1.54% and 2.54% respectively compared to conventional concrete (1.57%). Rice Husk Ash is an unideal replacement for cement as it is lightweight and highly amorphous, affecting the compressive strength of concrete to be severely lower than conventional concrete. Apart from that, Coconut Husk Fibre (CHF) and Palm Oil Fibre (OPF) analysed for degradation yielded up to 15% and 22% intensity reduction of present bonds respectively, after reaction with cement.